Model Pengaruh Kinerja Ekonomi Dan Kinerja Pasar Uang Terhadap Kinerja Bursa Efek Indonesia - Efraim Ferdinan Giri (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
Based on rule of thumb, economic growth will influence the capital market performance and financial market performance will affect the capital market performance. We use the Error correction model approach to analysis between variable. TARCH approach is employed, based on the ‘identification through heteroscedasticity’ technique, to estimate the impact of a change in the growth and kurs variable to IHSG. This study indicates that economic growth is not affect IHSG statistically significant in the short run, but positive statistically significant in the long run. This study show that increasing in $US exchange rate will lessening capital market performance. Additional analysis in this research shows the linear function model more proper than log-linear function model to predict this relationship.